Perencanaan Strategis Si/Ti Pada Dinas Cipta Karya, Tata Ruang Dan Kebersihan Kabupaten Kubu Raya Dengan Menggunakan Metodologi Tozer - - AMIK BSI Pontianak, Windi Irmayani (Speed - Sentra Penelitian Engineering dan Edukasi, 2016)
Abstract - Departmentof copyrighted work, spatial and hygiene districtof Kubu Raya experiencing operational constraints due to budget, facilities and human resources. These problems can be solved with the construction of information systems with the appropriate information technology. because the information systems and information technology can reduce operating costs and maximize existing human resources. It is necessary for Strategic Planning with Tozer Metodology to describes the detailed planning process constructions Information Systems/Information Technology. Phase 0is Determine the context and scope, phase 1 is Determining the Business and Information Regarding the need for support, phase 2 Evaluating Compliance Systems with Business Needs Current Options and Identify Solutions, phase 3 is Determining the Strategic Solutions, phase 4are Preparing and Conducting Implementation Plan.Key words: Information System,Information Technology, Tozer Metodology.